Influence of defect on the electrical and optical properties of A-site non-stoichiometry Ca0.67La0.22□0.11Ti(1−x)CrxO3−δ perovskite. Issue 34 (19th June 2019) - Hassen, A. B.; Rhouma, F. I. H.; Daoudi, M.; Dhahri, J.; Zaidi, M.; Abdelmoula, N.
Abstract : An investigation of the real part of permittivity for the compositions (a) x = 0 and (b) x = 0.1 solid solution Ca0.67 La0.22 □0.11 Ti(1− x ) Cr x O3− δ ceramics. Abstract : An investigation of the dielectric dispersion, electrical properties, scaling behavior and optical defects of Ca0.67 La0.22 □0.11 Ti(1− x ) Cr x O3− δ (CLT(1− x ) Cr x ) with x = 0 and x = 0.1 compositions is presented. The square in the formula is attributed to a vacancy in A-site. Relaxation phenomena were studied with dielectric and modulus formalism, while, the conductivity mechanism was investigated using electrical conductivity. A high permittivity of around 10 4, low dielectric loss and low electrical conductivity of around 10 −3 S cm −1 for Ca0.67 La0.22 TiO3 (CLT) was observed. These values make this composition interesting for microelectric applications. A comparison between the Z ′′ and M ′′ indicated that the short-range carrier motion dominates at low temperature and becomes less localized at high temperature. The optical defects of CLT and Ca0.67 La0.22 Ti0.9 Cr0.1 O3 (CLT0.9 Cr0.1 ) were studied by electron paramagnetic resonance (EPR) spectroscopy. The results suggest the formation of a [TiO6 ] 9− center, a (Ti 3+ – V O ) center, and dipole defect for CLT compound and Cr 3+ – V O center defect for CLT0.9 Cr0.1 compound. These defects are the source of the in-gap electron traps, which improve the optical properties of CLT(1− x ) Cr x and hence make it an interesting optical material for different applications.